New Generations of Rocket Engines - Dariusz Stanisław Sobolewski; Michał Amadeusz Sobolewski; Marek Juliusz Sobolewski; Joanna Paulina Sobolewska; Natalia Julia Sobolewska (JOURNAL OF ADVANCES IN PHYSICS, 2020)
The article, based on mathematical model of the space and particles revealed in "Theory of Space" (Sobolewski D. S., Theory of Space, 2016) (Sobolewski D. S., Theory of Space, 2017) and the description of the propagation of photons stated in publication entitled “Geometry of the Dark Matter and Preliminary Analysis of Alpha and Beta Photons’ Properties Based on Theory of Space” (Sobolewski, Sobolewski i Sobolewski, 2017), describes transverse waves propagating in space, including gravitational, fluctuating and matter waves. In particular, it focuses on waves of matter in which orientation of the spatial channels, connecting four-dimensional boundary hypersurfaces and , had been stabilised. For this type of the wave of matter the minimum energy value for deformation of boundary hypersurfaces of the matter waves has been appointed, which is smaller by several orders of magnitude than energy needed to change the orientation of vertical disturbances of space which connect four-dimensional boundary hypersurfaces and, The obtained results were used to introduce a new classification of rocket engines and to provide examples of their implementation. Furthermore, the article demonstrates first attempts to construct a rocket engine of the new type, including description of the principle of operation of the engine, which is subject of patent application entitled "HTS Photonic Rocket Engine" (Poland Patent nr P.421517, 2017), as well as presents an example of spacecraft shell implementation, which enables stabilization of orientation of its spatial channels. The Article thus reveals new perspectives for interplanetary travel through significant increase in spacecraft velocities, while simultaneously reducing the energy required to achieve them. In addition, the article describes interaction of photons with the boundary hypersurface , while determining the change in photon frequency depending on its curvature .